1963
DOI: 10.1149/1.2425705
|View full text |Cite
|
Sign up to set email alerts
|

The Anodic Behavior of Zinc in Potassium Hydroxide Solution

Abstract: A study of the anodic behavior of horizontal zinc electrodes in KOH solution has shown that the equationholds for concentrations in the range 1-13.8M and passivation times in the range 10-800 sec. The constant k depends on the KOH concentrations and attains a maximum value in the region of 8.5M KOH; i~, the maximum current density attainable without passivation, from a least squares fit is very near zero in all cases. From the linear parts of the curves connecting anode potential and time, values of dE/dT indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
0
1

Year Published

1966
1966
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(45 citation statements)
references
References 8 publications
3
41
0
1
Order By: Relevance
“…This time/polarization behavior resembled that previously reported by Hampson et al (11) for a planar electrode in unstirred electrolyte. About 3-5 sec before onset of the severe passivation, small white particles could be seen near the middle of the anode in the electrolyte, unattached to the surface as evidenced by a movement apparently in accord with small convective disturbances caused by the bubbles.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…This time/polarization behavior resembled that previously reported by Hampson et al (11) for a planar electrode in unstirred electrolyte. About 3-5 sec before onset of the severe passivation, small white particles could be seen near the middle of the anode in the electrolyte, unattached to the surface as evidenced by a movement apparently in accord with small convective disturbances caused by the bubbles.…”
Section: Resultssupporting
confidence: 90%
“…This was Paper 44 presented at the Atlanta, Georgia, Meeting of the Society, Oct. [9][10][11][12][13][14] 1977.…”
Section: Acknowledgmentmentioning
confidence: 99%
“…Zinc surface in alkaline solutions dissolves under the influence of a number of complex corrosion products formed on its surface [37][38][39]. Its reaction with hydroxyl ions of SPS initially forms zinc hydroxide:…”
Section: Discussionmentioning
confidence: 99%
“…The improved performance of passivated surface than unpassivated surface in controlling the corrosion of HDG in concrete pore solution may be explained by considering the reactions of zinc in alkaline solutions. Zinc dissolves in alkali under the influence of a number of complex corrosion products formed on its surface [15,16,41]. Its reaction with SPS initially produces zinc hydroxide:…”
Section: Discussionmentioning
confidence: 99%
“…In saturated lime solutions, the formation of a stable layer of calcium hydroxy zincate is reported [16,17]. In sodium and potassium hydroxide solutions, it was earlier presumed that the layers of corrosion products on zinc surface were complex and comprised of zinc oxide in combination with a porous layer of zinc hydroxide [41]. It was suggested that the zincate ions formed in Eq.…”
Section: Discussionmentioning
confidence: 99%